De oktoberrevolutie en de perestroika : de revolutie gaat door - terug naar Lenin - Sjatrov, Michael; Loginov, Vladlen; Koelesjov, Sergej (Moskou : Novosti, 1988)
Schenking Karel Maes
Nederlands
Monografie
Keywords: Lenin, Vladimir; Oktoberrevolutie; perestrojka